2020
DOI: 10.3390/molecules25173882
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrates Profile, Polyphenols Content and Antioxidative Properties of Beer Worts Produced with Different Dark Malts Varieties or Roasted Barley Grains

Abstract: The aim of this study was to assess the possibility of shaping properties of beers at the stage of brewing wort production with the use of various types of special malts (chocolate pale, chocolate dark, wheat chocolate, brown barley) and roasted barley grains. The carbohydrate profile, polyphenols content, antioxidant capacity, 5-hydroxymethylfurfural content, and the browning index level were analyzed. Statistical analysis showed significant differences in the values of the examined features between the sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 63 publications
4
35
1
Order By: Relevance
“…In fact, the thermal processing step is responsible of changes in the malt phenolic content because of chemical reactions as degradation, isomerization, polymerization, and Maillard reaction. 25 , 26 , 43 …”
Section: Results and Discussionmentioning
confidence: 99%
“…In fact, the thermal processing step is responsible of changes in the malt phenolic content because of chemical reactions as degradation, isomerization, polymerization, and Maillard reaction. 25 , 26 , 43 …”
Section: Results and Discussionmentioning
confidence: 99%
“…Maltotriose, maltose, and glucose contribute to the ethanol fermentation process with the use of S. cerevisie brewer’s yeast, therefore their content decreases during the process. Maltose is the main sugar of wort [ 23 ]. The wort contained 49.21–58.02 g/L maltose, 12.06–15.13 g/L maltotriose, 6.53–8.34 g/L glucose and 30.68–46.85 g/L dextrin.…”
Section: Resultsmentioning
confidence: 99%
“…For W0, it was 18.92 mg/L. The content of 5-HMF in brewing wort produced with the participation of 10% of various types of dark malt ranges from 5.54–24.31 mg/L, assuming the highest value for the wort produced with dark chocolate malt [ 23 ]. The wort, before hopping W0 obtained in the experiment, has a lower 5-HMF content.…”
Section: Resultsmentioning
confidence: 99%
“…It is only certain that substitution of barley malt with gelatinised legume seed malts might increase concentration of phenolic compounds in the wort (in the case of GC30 and GV30); however, it decreases its antioxidant properties. In the study conducted by Gąsior et al, it was shown that use of traditional beer brewing adjuncts, such as chocolate malts or roasted, unmalted barley, increased concentration of phenolic compounds as well as antioxidative properties of the worts to a greater extent than the addition of gelatinised legume seed malts conducted in this research [ 15 ].…”
Section: Discussionmentioning
confidence: 70%
“…These results show a possibility of using the malting process to improve the nutritional quality of legume seeds. The main advantages of malting over the sole germination process are the positive changes in the organoleptic characteristics of the finished product, as well as improved stability of malt over the germinated seed [ 15 ]. Legume malts could be used to produce gluten-free beer worts or malt extracts with high protein content, as well as to produce fermented food, such as tempeh, but with a reduced amount of antinutritional substances and an increased amount of antioxidants [ 2 , 3 , 8 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%